Effectiveness of Counterpressure Technique With a Birth Ball on Cervical Dilatation and Reduction of Labour Pain and Uterine Contractions: A Prospective Cohort Study - Egam, Adriana; Abdullah, Vera Iriani; Isir, Mariana; Duhita, Fitra; Mustamu, Alva Cherry (Scripta Medica, 2024)
Background/Aim: Non-pharmacological interventions play a crucial role in managing labour pain and facilitating labour progression. The counterpressure technique is a commonly utilised method purported to alleviate pain and enhance cervical dilation during childbirth. However, its effectiveness remains a subject of debate, necessitating further investigation. This study aimed to evaluate the efficacy of the counterpressure technique in managing labour pain and influencing labour progression among women in labour.Method: A randomised controlled trial was conducted involving participants in active labour. The intervention group received the counterpressure technique, while the control group received standard care. Pain levels, uterine contractions and cervical dilation were assessed and compared between the two groups.Results: Analysis revealed no significant difference in pain levels or uterine contractions between the intervention and control groups. However, there was a significant increase in cervical dilation in the intervention group compared to the control group (p = 0.034, Cohen's d = -0.586).Conclusion: Despite the counterpressure technique's limited impact on pain relief and uterine contractions, it significantly facilitated cervical dilation during labour. These findings contribute to understanding of non-pharmacological interventions in childbirth and underscore the importance of evidence-based approaches to labour management. Further research is warranted to elucidate the underlying mechanisms of the counterpressure technique and optimise its implementation in clinical practice.